ASSOCIATION BETWEEN EARLY TEMPERAMENT AND DEPRESSION AT 18 YEARS. Issue 9 (8th August 2014) - Bould, Helen; Araya, Ricardo; Pearson, Rebecca M.; Stapinski, Lexine; Carnegie, Rebecca; Joinson, Carol
<x xml:space="preserve">Abstract</x> Background Early childhood temperament, particularly negative emotionality (high tendency to show distress), may be a risk factor for subsequent depression. Methods Using data from a large UK cohort (Avon Longitudinal Study of Parents and Children), we examined the association between temperament on the Emotionality Activity Sociability Questionnaire at age 6 and ICD‐10 depression at 18. Results were adjusted for a range of confounders. Results Children with high emotionality scores at age 6 had a 20% (7–36%) increase in the odds of being diagnosed with depression at age 18. Conclusions Depression at 18 years has an early developmental diathesis, which means we may be able to identify children at risk of developing depression in young adulthood.